DETERMINASI KEPEMIMPINAN INTERPERSONAL, MOTIVASI, IKLIM ORGANISASI TERHADAP KOMITMEN ORGANISASI MELALUI KEPUASAN KERJA PADA DINAS PENDIDIKAN BATAM - Hidayat hidayat hidayat (PERADA, 2018)
ABSTRACT: This research is the result of a study of Interpersonal Leadership, Motivation, Organizational Climate, Job Satisfaction, and Organizational Commitment in Department of Education Batam Island. Collecting data in this study is done by distributing questionnaires in the form of questionnaires to 104 respondents with the status as an employee, the data obtained will then be tested using Path Analysis. Results of the analysis of the first path, directly variable Interpersonal Leadership, Motivation, Organizational Climate, significant effect on job satisfaction with the level of influence of variable percentage contribution of 30.7% whereas the results of the analysis of the second lane, directly variable Interpersonal Leadership, Motivation, Organizational Climate, not significant effect on the performance variables influence the level of the percentage contribution of 21.3 %. Keywords: Interpersonal Leadership, Motivation, Organizational Climate, Job Satisfaction, Organizational Commitment